2008
DOI: 10.1245/s10434-008-9955-5
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Dehydrogenase-5 (LDH-5) Expression in Human Gastric Cancer: Association with Hypoxia-Inducible Factor (HIF-1α) Pathway, Angiogenic Factors Production and Poor Prognosis

Abstract: The results of the current study show that LDH-5 expression may be a useful prognostic factor for patients with gastric carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
129
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(140 citation statements)
references
References 27 publications
7
129
1
3
Order By: Relevance
“…Our unexpected finding is that these NKG2D ligands might be derived from host immune cells rather than the tumors. Prior studies have reported that cancer patients with elevated amounts of LDH in sera have a poor prognosis (13)(14)(15)24). Although this poor prognosis might simply reflect larger tumor burdens, the secretion of LDH also might contribute to the immune evasion of these cancers by its induction of NKG2D ligands on host myeloid cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our unexpected finding is that these NKG2D ligands might be derived from host immune cells rather than the tumors. Prior studies have reported that cancer patients with elevated amounts of LDH in sera have a poor prognosis (13)(14)(15)24). Although this poor prognosis might simply reflect larger tumor burdens, the secretion of LDH also might contribute to the immune evasion of these cancers by its induction of NKG2D ligands on host myeloid cells.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, the role of mitochondria in tumor cells has been controversial because many tumor cell lines with high proliferative rates do not have defects in their oxidative metabolism. 9 Although lactate dehydrogenase A (LDH-A) is overexpressed in several tumors including gastric cancer, head and neck carcinoma, lung cancer and others, [10][11][12] it has been shown that LDH-A knocked out tumor cells maintain a substantial capacity to produce ATP by oxidative phosphorylation. 13 Mitochondria participate in important cellular processes, such as ATP production, reactive oxygen species (ROS) generation, apoptosis and the synthesis of metabolites that serve as building blocks for biomolecules.…”
Section: Warburg Effect or Aerobic Glycolysismentioning
confidence: 99%
“…이러한 LDH 동위효소 발현양상은 사람에서 LDH A4 동위효소의 증가양상을 보이는 바이러스성 간염 [3]과 위암 [25], B4 동위효소의 증가양상을 나 타내는 급성심근경색 [32]과 중증급성호흡기증후군 [28], testis-specific LDH C4 동위효소의 제한된 발현양상을 보이는 악 성종양 [26] 등 여러 병증의 진단 및 어류의 진화, 계통학적 분 석 [1,29,42]에 다양하게 이용된다.…”
Section: 서 론unclassified